2002
DOI: 10.1021/jf020497r
|View full text |Cite
|
Sign up to set email alerts
|

Chemometrical Analysis of 18 Metallic and Nonmetallic Elements Found in Honeys Sold in France

Abstract: The elemental analysis of 86 honeys sold in France was performed with an inductively coupled plasma atomic emission spectrometer in order to measure significant concentrations of Ag, Ca, Cr, Co, Cu, Fe, Li, Mg, Mn, Mo, P, S, Zn, Al, Cd, Hg, Ni, and Pb. Principal component analysis, correspondence factor analysis, and hierarchical cluster analysis were used to rationalize and interpret the analytical data. Crude relationships were found between the elemental profiles of the honeys and their botanical origin. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
69
6
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 12 publications
15
69
6
3
Order By: Relevance
“…Chudzinska & Baralkiewicz, [2010] analysed fi fty-fi ve Polish honey samples to rationalize and interrupt the analytical data for the determination of thirteen metallic and nonmetallic elements by using PCA tool. Similar study was reported by Devillers et al [2002] who examined French honeys.…”
Section: Introductionsupporting
confidence: 87%
“…Chudzinska & Baralkiewicz, [2010] analysed fi fty-fi ve Polish honey samples to rationalize and interrupt the analytical data for the determination of thirteen metallic and nonmetallic elements by using PCA tool. Similar study was reported by Devillers et al [2002] who examined French honeys.…”
Section: Introductionsupporting
confidence: 87%
“…The Swiss MRL for Ni varies between 0.1 mg/kg (beer) to 0.2 mg/kg (edible fat). Following levels have been found in honey: Ni: 0.004-3.23 mg/kg (Porrini et al, 2002); < 0.001 mg/kg, (Devillers et al, 2002b); 0.09-0.34 mg/kg (Devillers et al, 2002c). In honey samples from contaminated and uncontaminated areas of Slovakia Hg levels ranged from 0.050 to 0.212 mg/kg and from 0.001 to 0.003 mg/kg, respectively (Toporèak et al, 1992).…”
Section: Heavy Metalsmentioning
confidence: 96%
“…In honey samples from contaminated and uncontaminated areas of Slovakia Hg levels ranged from 0.050 to 0.212 mg/kg and from 0.001 to 0.003 mg/kg, respectively (Toporèak et al, 1992). In two recent studies no Hg could was in 150 French acacia honeys above the detection limit of 0.0005 mg/kg (Devillers et al, 2002b) or in 86 honey samples of different botanical and geographical origin sold in France (Devillers et al, 2002c). In a Polish study, Hg levels were measured in different bee products were studied and the following values in mg/kg were reported: propolis: 0.001-0.07, beeswax: 0.0001-0.06, honey: 0.00001-0.006 (Madras-Majevska et al, 2002).…”
Section: Heavy Metalsmentioning
confidence: 97%
“…Inductively coupled plasma optical emission spectrometry (ICP OES) is commonly used for measuring concentrations of Li in honeys, typically along with other metals. [1][2][3][4][5][6] Flame optical emission spectrometry (FOES), although more inexpensive than ICP OES is curiously rarely used. [7][8][9][10] In case of both mentioned techniques, samples of honey are usually calcined, followed by dissolving resulted ash in solutions of mineral acids [3][4][5][6] or digested in concentrated oxidizing reagents 1,2 before measuring Li concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was expected that this procedure would be a good alternative to commonly used acid decomposition or calcinations of honey. [1][2][3][4][5][6] In advance, the effect of various concentrations of K, Na, glucose and fructose, being the most important constituents of honeys, on the Li response was studied. The sorption behavior of Li and mentioned constituents toward different sorption materials, including an adsorbing resin Amberlite XAD-7HP, a strongly basic anion-exchange resin Dowex 1×4-200, a strongly acidic cation-exchange resin Dowex 50W×8-200 and a mixed bed ion-exchange resin Dowex Retardion 11A8, was examined as well.…”
Section: Introductionmentioning
confidence: 99%